2020
DOI: 10.1590/1982-0275202037e190139
|View full text |Cite
|
Sign up to set email alerts
|

Internal structure of the Parenting Practices Scales in a vulnerable sample: a confirmatory factor analysis

Abstract: Abstract The objective of this study was to assess the internal structure of the Brazilian version of the Parenting Practices Scales, examining its dimensionality and the internal consistency of their subscales in a sample of vulnerable young individuals (N = 452). The six-factor structure was replicated through Confirmatory Factor Analysis; however, Cronbach’s alpha values for two factors indicated poor internal consistency: autonomy granting (α = 0.55) and punitive control (α = 0.51). Considering the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Previous studies used three factors of the instrument (out of six) to assess specific parenting practices, namely parental supervision, intrusiveness, and emotional support (Murta et al, 2020a(Murta et al, , 2020b and followed the scoring recommendations of Teixeira et al (2006). The present study used all size items and scored the instrument as continuous variables along the two main dimensions of responsiveness and demandingness, following the recommendations of Pinheiro-Carozzo et al (2020). Therefore, previous studies assessed parenting practices, while this study assessed parenting styles.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Previous studies used three factors of the instrument (out of six) to assess specific parenting practices, namely parental supervision, intrusiveness, and emotional support (Murta et al, 2020a(Murta et al, , 2020b and followed the scoring recommendations of Teixeira et al (2006). The present study used all size items and scored the instrument as continuous variables along the two main dimensions of responsiveness and demandingness, following the recommendations of Pinheiro-Carozzo et al (2020). Therefore, previous studies assessed parenting practices, while this study assessed parenting styles.…”
Section: Discussionmentioning
confidence: 98%
“…However, because these families were included in the same group and treated as one, any improvements in some subgroups may be negated by deteriorations in other subgroups, resulting in a much lower effect or even none at all. In addition, a psychometric study of a sample of vulnerable people indicated that the appropriateness of the adopted instrument increased when the main two latent dimensions, demandingness and responsiveness, were used as continuous variables rather than assessing the six independent parenting practices of punitive control, behavioral supervision, demand for responsibility, emotional support, autonomy granting, and intrusiveness (Pinheiro-Carozzo, Gato, Fontaine, & Murta, 2020). Thus, we hypothesize that the impact of SFP varies according to parenting style, and this may help parents to develop the weaker dimension of their specific styles and consequently achieve better parenting outcomes when raising their children.…”
Section: The Present Studymentioning
confidence: 99%
See 2 more Smart Citations